The Effectiveness of the Problem-Based Learning Model on Students’ Mathematical Creative Thinking Ability - Lois Tambunan (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
The purpose of this study is to determine the effectiveness of the Problem-Based Learning (PBL) model on students’ mathematical creative thinking ability in the topic of circles in Grade XI at SMA Negeri 1 Siantar. The research design used in this study is the One-Shot Case Study Design. The population consists of all Grade XI students at SMA Negeri 1 Siantar, with the sample being class XI-2, totaling 36 students, selected using Cluster Random Sampling. Data collection was conducted using a test that had been previously validated. The descriptive analysis results showed an average test score of 87.75. Data analysis was performed using a t-test, which resulted in a significance value of 0.00 < 0.05 and a tcalculated value of 9.922 > ttable value of 2.03. Based on these findings, it can be concluded that the Problem-Based Learning model has a positive and significant effect on students' mathematical creative thinking ability in the topic of circles.